Hebrews and the sanctuary in heaven - Malheiros, Isaac (Vox Scripturae - Revista Teológica Internacional, 2017)
The concept of a heavenly sanctuary is well attested in Hellenistic Jewish literature, in jewish apocalyptic literature, in Qumran texts and in the Old Testament. Through the method of literature review and analysis of some primary sources, this study will evaluate the possible conceptual backgrounds of Hebrews, and this will reveal that the “sanctuary in heaven” model is more easily justifiable that the “sanctuary as cosmos” model, associated with the Hellenistic Judaism. The close relationship between Hebrews, the Old Testament and the jewish apocalyptic literature makes it possible to conclude that Hebrews reflects the concept of a actual heavenly sanctuary (not metaphorical), in heaven (not cosmological), with two rooms, where there is already priestly activity.